What is the evidence of impaired motor skills and motor control among children with attention deficit hyperactivity disorder (ADHD)? Systematic review of the literature - Kaiser, M.-L.; Schoemaker, M.M.; Albaret, J.-M.; Geuze, R.H. (Research in developmental disabilities, 2015)
•Motor skills are often impaired among ADHD children, the degrees of severity vary from light to severe impairment.•Motor deficit in fine and/or gross motor skills can be found.•More than half of the ADHD children improve motor skills under medication.•Different explanations of the motor skill deficits can be given: comorbidity, inattention or lack of inhibition. This article presents a review of the studies that have analysed the motor skills of ADHD children without medication and the influence of medication on their motor skills. The following two questions guided the study: What is the evidence of impairment of motor skills and aspects of motor control among children with ADHD aged between 6 and 16 years? What are the effects of ADHD medication on motor skills and motor control? The following keywords were introduced in the main databases: attention disorder and/or ADHD, motor skills and/or handwriting, children, medication. Of the 45 articles retrieved, 30 described motor skills of children with ADHD and 15 articles analysed the influence of ADHD medication on motor skills and motor control. More than half of the children with ADHD have difficulties with gross and fine motor skills. The children with ADHD inattentive subtype seem to present more impairment of fine motor skills, slow reaction time, and online motor control during complex tasks. The proportion of children with ADHD who improved their motor skills to the normal range by using medication varied from 28% to 67% between studies. The children who still show motor deficit while on medication might meet the diagnostic criteria of developmental coordination disorder (DCD). It is important to assess motor skills among children with ADHD because of the risk of reduced participation in activities of daily living that require motor coordination and attention.